An open-source GIS user interface for the TARGET climate model in the Urban Multi-scale Environmental Predictor (UMEP) tool - Jixuan Chen; Peter M. Bach; Matthias Demuzere; João P. Leitão; Fredrik Lindberg; Kerry A. Nice; Nils Wallenberg (Environmental Modelling & Software, 2026)

Investigating the efficacy of a fast urban climate model for spatial planning of green and blue spaces for heat mitigation - Jixuan Chen; Peter M. Bach; Kerry A. Nice; João P. Leitão (Science of The Total Environment, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Host plant associations and geography interact to shape diversification in a specialist insect herbivore - Amanda L. Driscoe; Chris C. Nice; Robert W. Busbee; Glen R. Hood; Scott P. Egan; James R. Ott (Molecular Ecology, 2019)
Disentangling the processes underlying geographic and environmental patterns of biodiversity challenges biologists as such patterns emerge from eco‐evolutionary processes confounded by spatial autocorrelation among sample units. The herbivorous insect, Belonocnema treatae (Hymenoptera: Cynipidae), exhibits regional specialization on three plant species whose geographic distributions range from sympatry through allopatry across the southern United States. Using range‐wide sampling spanning the geographic ranges of the three host plants and genotyping‐by‐sequencing of 1,217 individuals, we tested whether this insect herbivore exhibited host plant‐associated genomic differentiation while controlling for spatial autocorrelation among the 58 sample sites. Population genomic structure based on 40,699 SNPs was evaluated using the hierarchical Bayesian model entropy to assign individuals to genetic clusters and estimate admixture proportions. To control for spatial autocorrelation, distance‐based Moran's eigenvector mapping was used to construct regression variables summarizing spatial structure inherent among sample sites. Distance‐based redundancy analysis (dbRDA) incorporating the spatial variables was then applied to partition host plant‐associated differentiation (HAD) from spatial autocorrelation. By combining entropy and dbRDA to analyse SNP data, we unveiled a complex mosaic of highly structured differentiation within and among gall‐former populations finding evidence that geography, HAD and spatial autocorrelation all play significant roles in explaining patterns of genomic differentiation in B. treatae . While dbRDA confirmed host association as a significant predictor of patterns of genomic variation, spatial autocorrelation among sites explained the largest proportion of variation. Our results demonstrate the value of combining dbRDA with hierarchical structural analyses to partition spatial/environmental patterns of genomic variation.

Extreme heterogeneity of population response to climatic variation and the limits of prediction - Chris C. Nice; Matthew L. Forister; Joshua G. Harrison; Zachariah Gompert; James A. Fordyce; James H. Thorne; David P. Waetjen; Arthur M. Shapiro (Global Change Biology, 2019)
Certain general facets of biotic response to climate change, such as shifts in phenology and geographic distribution, are well characterized; however, it is not clear whether the observed similarity of responses across taxa will extend to variation in other population‐level processes. We examined population response to climatic variation using long‐term incidence data (collected over 42 years) encompassing 149 butterfly species and considerable habitat diversity (10 sites along an elevational gradient from sea level to over 2,700 m in California). Population responses were characterized by extreme heterogeneity that was not attributable to differences in species composition among sites. These results indicate that habitat heterogeneity might be a buffer against climate change and highlight important questions about mechanisms maintaining interpopulation differences in responses to weather. Despite overall heterogeneity of response, population dynamics were accurately predicted by our model for many species at each site. However, the overall correlation between observed and predicted incidence in a cross validation analysis was moderate (Pearson's r = 0.23, SE 0.01), and 97% of observed data fell within the predicted 95% credible intervals. Prediction was most successful for more abundant species as well as for sites with lower annual turnover. Population‐level heterogeneity in response to climate variation and the limits of our predictive power highlight the challenges for a future of increasing climatic variability.

Understanding a migratory species in a changing world: climatic effects and demographic declines in the western monarch revealed by four decades of intensive monitoring - Anne E. Espeset; Joshua G. Harrison; Arthur M. Shapiro; Chris C. Nice; James H. Thorne; David P. Waetjen; James A. Fordyce; Matthew L. Forister (Oecologia, 2016)

Regional population differentiation in the morphologically diverse, elevationally widespread Nearctic skipper Polites sabuleti - Joshua P. Jahner; Matthew L. Forister; Chris C. Nice; James A. Fordyce; Joseph S. Wilson; Dennis D. Murphy; Zachary H. Marion; Arthur M. Shapiro (Journal of Biogeography, 2015)
Aim To evaluate three phylogeographical models associated with the presence of mountains (montane vicariance, sky island and parapatry) as drivers of intraspecific diversification in the sandhill skipper, Polites sabuleti (Lepidoptera: Hesperiidae), a morphologically variable species found in a variety of habitats from sea level to the alpine zone. Location Western North America. Methods The mitochondrial cytochrome c oxidase subunit II region was sequenced in 189 P. sabuleti individuals. Mitochondrial sequences were used in a spatial analysis of molecular variance ( SAMOVA ) to evaluate geographical population structure. AFLP markers were also generated for 347 individuals in order to estimate admixture proportions and examine population differentiation based on the nuclear genome. Results Twenty‐five mitochondrial haplotypes and 42 anonymous AFLP loci were found across 36 collection localities. Mitochondrial variation suggests a degree of regional population structure, although at least one of the inferred population groups extends over nearly the entire geographical range of the species. Analyses of nuclear data ( AFLP s) identified five genetic clusters, including one restricted to high elevations in the Sierra Nevada. Main conclusions The distribution of genetic variation within Polites sabuleti , a species with a broad elevational range, does not strictly support either mountain‐associated vicariance or ‘sky island’ isolation as the dominant process. Instead, we find complex population structure, including evidence for divergence between high‐ and low‐elevation populations in the Sierra Nevada mountains.

The evolution of novel host use is unlikely to be constrained by trade‐offs or a lack of genetic variation - Zachariah Gompert; Joshua P. Jahner; Cynthia F. Scholl; Joseph S. Wilson; Lauren K. Lucas; Victor Soria‐Carrasco; James A. Fordyce; Chris C. Nice; C. Alex Buerkle; Matthew L. Forister (Molecular Ecology, 2015)
The genetic and ecological factors that shape the evolution of animal diets remain poorly understood. For herbivorous insects, the expectation has been that trade‐offs exist, such that adaptation to one host plant reduces performance on other potential hosts. We investigated the genetic architecture of alternative host use by rearing individual Lycaeides melissa butterflies from two wild populations in a crossed design on two hosts (one native and one introduced) and analysing the genetic basis of differences in performance using genomic approaches. Survival during the experiment was highest when butterfly larvae were reared on their natal host plant, consistent with local adaptation. However, cross‐host correlations in performance among families (within populations) were not different from zero. We found that L. melissa populations possess genetic variation for larval performance and variation in performance had a polygenic basis. We documented very few genetic variants with trade‐offs that would inherently constrain diet breadth by preventing the optimization of performance across hosts. Instead, most genetic variants that affected performance on one host had little to no effect on the other host. In total, these results suggest that genetic trade‐offs are not the primary cause of dietary specialization in L. melissa butterflies.

Specificity, rank preference, and the colonization of a non-native host plant by the Melissa blue butterfly - M. L. Forister; C. F. Scholl; J. P. Jahner; J. S. Wilson; J. A. Fordyce; Z. Gompert; D. R. Narala; C. Alex Buerkle; C. C. Nice (Oecologia, 2013)